Pollution Levels and Determinants of Water Health In The Citarum River, Muara Gembong Bekasi, West Java - Awifan Krisnanti, Sukma; Awifan Dwijaya, Bayu (Ridwan Institute, 2021)
Restoration of water quality needs attention at rivers in Indonesia. Land occupation and land conversion are the main problems that have an impact on the handling of water quality in the Muara Gembong area. The research location in the field administratively is in Muara Gembong District, Bekasi Regency, West Java.Testing the quality of river water in this study was carried out directly in the field using digital measuring instruments including pH (electrometic principle), water temperature (mechanical expansion principle), DO (membrane polarography principle), TDS (electrometric principle), Phosphate (calorimetric principle), Brightness (measurement of distance units) and Salinity (principle of refraction). As for the TSS (gravimetric principle) and BOD (membrane polarographic principle) parameters, the test was carried out in Laboratory at the Secretariat of the Indonesian Biodiversity Conservation Unit (IBCU). The results of the Pollution Index showed that the research location was divided into 3 groups, namely moderate pollution (upstream and Muara Mekar), light pollution (Middle, Muara Bendera, Beting and Muara Bungin) and good condition (Muara Kuntul). The results of PCA analysis with a variance value of 60.458% showed that the location of the study was holistically affected by TSS and phosphate content as the dominant environmental parameters determining environmental conditions.